PELATIHAN PERSONALITY DEVELOPMENT BAGI DOSEN DAN TENAGA KEPENDIDIKAN JURUSAN KEBIDANAN POLTEKES KEMENKES DI AKPAR SILIWANGI - R. Soni Sumali ,; Tuti Iriani ,; Moh. Abdul Azis Danu Brata ,; Indah Sugiarti ,; Mila Karmila , (JURNAL PENGABDIAN MANDIRI, 2025)
Personality Development Training aims to improve the interpersonal and professional competence of lecturers and educational staff in the Midwifery Department of the Ministry of Health Polytechnic at the Siliwangi Tourism Academy. In the world of education, a good personality is an important factor in creating a conducive learning environment. This training covers various aspects of self-development, such as communication, emotional management, and professional ethics. This community service method uses a participatory approach with a combination of lectures, group discussions and practical simulations. The evaluation results show that the training had a positive impact on increasing awareness of the importance of personality development in supporting academic and administrative tasks.